Living Memorial: A Case Study on the Creation of Memorial Stadiums at the University of Illinois, University of Minnesota, and Indiana University during the 1920s - Swick, Jeremy E. (My University, 2017)
This thesis presents three case studies of the "Memorial Stadiums" and other campus buildings created at the University of Illinois -Urbana-Champaign, the University of Minnesota - Twin Cities, and Indiana University - Bloomington following the completion of World War I. These case studies, utilizing primary sources including, but not limited to, newspapers, correspondence, campaign records, university yearbooks, among other archival material from the three universities studied explore the reasons behind the creation of the stadiums and various buildings on the campuses. These case studies also examine how the various building projects gained and maintained support from students, alumni, staff, and general public. This topic was selected because the history of these three stadiums, all built around the same time, and with the same name, have not received extensive research in this manner.
Keywords: Sports facilities; University of Illinois at Urbana-Champaign--Football--History; College sports--United States; Indiana University, Bloomington-- Football--History; Football; Stadiums--Social aspects--United States; University of Minnesota--Football-- History; College sports--United States; Universities and colleges